Degradation of Crude Oil Spills in Marine Waters Using Ultra Filtration Membranes and Biological Processes - N. Hendrasarie; E. Susanti (Future Science)
Degradation of crude oil using ultra filtration membrane and the bioligical process is aim to get result of more effective processing. This membrane ability able to shift the ascription waste as cost becoming waste as profit. This matter gives the positive implication not only industrial party because process almost always profit, inclusive of for environment continuity which is uncared frequently. Process biologist used system aeration with the aerobic bacteria coming from seeding of waste of itself oil, environmental friendly so that. To process the ultra filtration membrane, using pressure difference, temperature and rate of flow which vary and stay in a series of reactor, so that easy to operational. Process of biologic to degraded BOD, color, paraffin, oil and grease, happened by the parameter degradation more than 50%, with the improvement DO more than 50%, while COD, phenol, ammonia, and its pH less than 50%. Process of Ultra filtration (UF) Membrane to degraded more than 50%, are: BOD, COD, Phenol, Ammonia, Paraffin, Color, Oil and Grease. The pH which at the most 50%. The result of this research, can be evaluated from excess and insufficiency from each process which can be seen from some factor, like operational factor, fund factor, and experienced factor. In this study, it was found that membrane ultra filtration was more effective in reducing the organic content in the spill of crude oil in marine waters than biological processes.